Efek Larvasida Bakteri Kitinolitik dari Limbah Kulit Udang terhadap Larva Aedes aegypti - Dyah Widiastuti; Dewi Marbawati (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Aedes aegypti is a major vector for Dengue, a deadly disease causing death of millions of people in developing countries both in urban and rural populations. Ae. aegypti control using chemical insecticide was always carried out and lead to a widespread insecticide resistance. Therefore, mosquito biological control is needed to replace the usage of chemical insecticide. A chitinolytic bacteria, was isolated from shrimp’s waste (head and shell). The isolate showed chitinolytic activity as a transparent zone in colony inside the synthetic media, containing (w/v)- 0,3 % colloidal chitin, 1% pepton, 0,5% yeast extract, 0,1% NaCl, 0,1% K2HPO4, 0,05% MgSO4.7H2O, 0,001% FeSO4.7H2O, 0,001% ZnSO4.7H2O, and each of 0,0001% CuSO4.5H2O, MnSO4.nH2O and CaCl2.2H2O at pH 7 and 300C after 72 h of incubation. The isolate was identified as gram positive group based on gram staining. In the experimental method, four concentrations of chitinolytic bacteria (4%, 8%, 16% and 32%) was exposed to Ae. aegypti larvae. The result showed that chitinolytic bacterium degrades exoskeleton of third instar larvae of Ae. aegypti. Degradation of exoskeleton started on the 2nd days and occurred in thorax region. Probit analysis showed LC50 value was obtaninedat concentration of 2%.